Role of the Regional economic communities (RECs) in Information and Communication Technologies (ICT) in the Asia-Pacific - Ngo Thi Thanh Loan; Hitoshi Mitomo (International Telecommunications Society (ITS), 2017)
In this article, we review Information and Communication Technologies (ICT) policymaking and regulation of the regional economic communities (RECs) in conjunction with their regional regulators' associations (RRAs) in the region of Asia-Pacific.Undoubtedly, this regulatory structure has been drafted with a regional mindset: to promote the harmony among members and to form regional associations in hope of stimulating cross-border cooperation and market development. This paper focuses on the political and legal aspects of ICT regulatory policies, the development and the rising number of cooperation programs as well as the visions of RECs and RRAs in the Asia-Pacific. By employing the framework of regulatory regionalism, particularly on the idea that the policies can be conceptualized as a territorial political system taking place in the institutional space of the state, we explore different implementations of regional regulations on ICT that are essential to understand the dynamics of new mode of regional governance.
Keywords: 330; regional governance; regulatory regionalism; ICT policy & regulation